Nurses' experiences of home care: A qualitative study - Atefeh Shamsi; Ahmadreza Yazdannik; Nayereh Naseri (Preventive Care in Nursing and Midwifery Journal)
Background: Addressing the challenges of home care is crucial for transforming traditional care models into modern healthcare systems. Objectives: The current study aimed to explore nurses' experiences of home care challenges. Methods: The study was designed using a qualitative approach to explore the experiences of twenty-two Iranian nurses across three cities in 2022-2023. Data collection was performed using semi-structured interviews based on exploring the nurses' experiences. Data analysis was conducted using the Lundman and Graneheim content analysis method. Results: The study revealed five main categories of challenges, including "the need for improved education", "political support", "professional resources", "social acceptance", and "financial models". Conclusion: It is crucial to establish a foundation of academic programs, comprehensive legislation, political support, and financial models to develop home care services. This study provides worthwhile insights into the challenges nurses face in-home care and highlights the necessity of addressing insufficiencies to improve the quality and accessibility of homecare services.